Intrinsic risk factors for gross motor delay in children aged 6-24 months - Joanna Erin Hanrahan; Irawan Mangunatmadja (Indonesian Pediatric Society, 2019)
Background. Gross motor is one of the skill domain with the highest parental concern as mastering it determines the autonomy of a child. Several internal risk factors including perinatal asphyxia, prematurity, low birth weight, wide fontanelle, and microcephaly have been studied in predicting gross motor delay with varied results. This study is made to arrange a strategic intervention on the prevention of delayed development. Objective. To evaluate perinatal asphyxia, gestation age <37 weeks, birth weight <2500 grams, microcephaly, and wide fontanelle as predictors of gross motor delay in children aged 6-24 months. Methods. A case control study design was used. Data collection was conducted by direct assessment of gross motor skill and parents’ interview in Cipto Mangunkusumo National Hospital and Anakku Clinic, South Jakarta. Children with gross motor delay were included in the case group and children with normal gross motor were included in the control group. Data was analyzed using bivariate and multivariate analysis with a statistical significance value of P<0.05 and 95% confidence intervals. Results. One hundred and twenty-six subjects were studied, with 63 children in the case group and 63 children in the control group. Baseline characteristics of subjects were similar between the two groups. Microcephaly and gestation age <37 weeks were predictors of gross motor delay [(aOR 4.613 (95% CI 95 2.023 to 10.521, P<0.001) and (aOR 3.668 (95% CI 1.153 to 11.673, P=0.028), respectively]. Conclusion. Microcephaly and gestation age <37 weeks are significant predictors of gross motor delay in children aged 6-24 months.